Impact of Timing on Efficacy and Safetyof Intracoronary Autologous Bone Marrow Stem Cells Transplantation in Acute Myocardial Infarction: A Pooled Subgroup Analysis of Randomized Controlled Trials - Zhang, Shuning (Clin Cardiol, 2009)
BACKGROUND: Until now there were no clinical studies or systematic reviews to investigate the impact of timing on efficacy and safety of intracoronary bone marrow stem cell (BMSC) transfer in patients with acute myocardial infarction (AMI). HYPOTHESIS: Timing of BMSC administration might play an important role in the therapeutic response in AMI patients. METHODS: A systematic literature search of PubMed, MEDLINE, and Cochrane Evidence‐Based Medicine (EBM) databases was made on randomized controlled trials with at least 3‐month follow‐up data for patients with AMI undergoing emergent percutaneous coronary intervention (PCI) and receiving intracoronary BMSC transfer thereafter. RESULTS: A total of 7 trials with 660 patients were available for analysis. Compared to baseline level, BMSC transfer at 4 to 7 days post‐AMI significantly improved left ventricular ejection fraction (LVEF; 4.63% increase, 95% confidence interval [CI]: 1.00%‐8.26%, P = 0.01), reduced left ventricular (LV) end‐systolic dimensions (95% CI: − 0.53 − 0.02, P = 0.03), decreased the incidences of revascularization (odds ratio [OR]: 0.60, 95% CI: 0.37–0.97, P = 0.04), decreased the cumulative clinical events of death or recurrent myocardial infarction (OR: 0.32, 95% CI: 0.11–0.95, P = 0.04), and decreased culprit artery restenosis or ventricular arrhythmia (OR: 0.59, 95% CI: 0.36–0.96, P = 0.03) however these improvements did not reach statistical significance in emergent transfer trials (within 24 hour post‐AMI). Compared with emergent transfer, intracoronary BMSC therapy at 4 to 7 days also significantly reduced the incidence of revascularization (P for interaction = 0.02). CONCLUSIONS: BMSC transfer at 4 to 7 days post‐AMI was superior to that within 24 hours in improving LVEF, decreasing LV end‐systolic dimensions, and reducing the incidence of revascularization. Copyright © 2009 Wiley Periodicals, Inc.